Development of Experimental LKPD Using Virtual PhET Lab Simulation Media to Improve Learning Outcomes and Students Enthuasiasim in Acid-Base Materials for Class XI In SMA - Ima Purnamasari; Achmad Lutfi (Universitas Lampung, 2021)
Media learning can stimulate the enthusiasm of participants raised in learning activities. This study is aimed at determining whether the LKPD learning media experiments with PhET virtual laboratory simulation media on developed acid and base learning eyes have met validity, practicality, and efficiency. The subjects of this study were 25 students of class 12 SMA Muhammadiyah 10 GKB Gresik using the 3D(define,design, dan develop) development model developed by Thiagarajan. The results obtained are, 1) Validity of the LKPD experiment declared valid on the validity of the contents and validity of the consecutive structure obtained a percentage of 87.5% and 84.3% with very worthy criteria. 2) The practicality of the LKPD developed is said to be practical by increasing the comfort response of participants when using the LKPD with an average percentage of 98.1% with very practical criteria. 3) Assessed from the increased enthusiasm of the participants against the experimental LKPD which obtained an average percentage of 99% with one effective criterion, and the student's learning value increased on basic acid which shows an increase, and specified in the effective category with an average percentage of N-Gain of 80%. And stated to have learned from its classic sequence.Keywords: LKPD eksperimen,simulasi PhET, asam basaDOI: 10.23960/jppk.v10.i3.2021.20